Validity and reliability of the self-regulation martial arts questionnaire (SR-MAQ): A study in 3 types of martial arts - Alif, Muhammad Nur; Komarudin; Muhtar, Tatang; Mulyana (Journal Sport Area, 2024)
Background Problems: Self-regulation, which includes positive behavior, metacognitive awareness, and motivation, is critical to adolescents' development.  Despite its benefits in structured activities such as martial arts, there is a lack of existing tools to assess self-regulation among adolescent martial arts participants. This study addresses this gap by developing an instrument to measure adolescents' self-regulation abilities. Research Objectives: This research aims to adapt an instrument in the form of a questionnaire to measure self-regulation in martial arts activities. Methods: The author uses the cross-cultural adaptation method. Adapting research instruments is not just a language change. There is an aspect of cross-cultural adaptation that is important so that the research instrument can measure what it should measure (valid) and be reliable (consistent in measurement). A total of 58 participants were involved in three stages of instrument validity, consisting of 21 pencak silat students, 18 karate students, and 19 taekwondo students who were selected proportionally. Findings/Results: After data analysis, the results of this research are 67 SR-MAQ question items declared valid and reliable. Conclusion: The development of the SR-MAQ instrument allows for the measurement of the self-regulation of teenage martial arts practitioners, contributing to their positive development. To expand the utility and generalisability of this instrument, we need further research involving a wider age range and participants from different types of martial arts. This will not only increase the relevance of the findings but also provide richer insights into the role of self-regulation in various adolescent activity contexts.